Plant-Derived Toxin Inhibitors as Potential Candidates to Complement Antivenom Treatment in Snakebite Envenomations - Adrião, Asenate A. X.; dos Santos, Aline O.; de Lima, Emilly J. S. P.; Maciel, Jéssica B.; Paz, Weider H. P.; da Silva, Felipe M. A.; Pucca, Manuela B.; Moura-da-Silva, Ana M.; Monteiro, Wuelton M.; Sartim, Marco A.; Koolen, Hector H. F. (Frontiers in Immunology, 2022)
Snakebite envenomations (SBEs) are a neglected medical condition of global importance that mainly affect the tropical and subtropical regions. Clinical manifestations include pain, edema, hemorrhage, tissue necrosis, and neurotoxic signs, and may evolve to functional loss of the affected limb, acute renal and/or respiratory failure, and even death. The standard treatment for snake envenomations is antivenom, which is produced from the hyperimmunization of animals with snake toxins. The inhibition of the effects of SBEs using natural or synthetic compounds has been suggested as a complementary treatment particularly before admission to hospital for antivenom treatment, since these alternative molecules are also able to inhibit toxins. Biodiversity-derived molecules, namely those extracted from medicinal plants, are promising sources of toxin inhibitors that can minimize the deleterious consequences of SBEs. In this review, we systematically synthesize the literature on plant metabolites that can be used as toxin-inhibiting agents, as well as present the potential mechanisms of action of molecules derived from natural sources. These findings aim to further our understanding of the potential of natural products and provide new lead compounds as auxiliary therapies for SBEs.